Nucleosome Assembly and Disassembly in vitro Are Governed by Chemical Kinetic Principles - Zhao, Hongyu; Guo, Mingxin; Zhang, Fenghui; Shao, Xueqin; Liu, Guoqing; Xing, Yongqiang; Zhao, Xiujuan; Luo, Liaofu; Cai, Lu (Frontiers in Cell and Developmental Biology, 2021)
As the elementary unit of eukaryotic chromatin, nucleosomes in vivo are highly dynamic in many biological processes, such as DNA replication, repair, recombination or transcription, to allow the necessary factors to gain access to their substrate. The dynamic mechanism of nucleosome assembly and disassembly has not been well described thus far. We proposed a chemical kinetic model of nucleosome assembly and disassembly in vitro. In the model, the efficiency of nucleosome assembly was positively correlated with the total concentration of histone octamer, reaction rate constant and reaction time. All the corollaries of the model were well verified for the Widom 601 sequence and the six artificially synthesized DNA sequences, named CS1-CS6, by using the salt dialysis method in vitro. The reaction rate constant in the model may be used as a new parameter to evaluate the nucleosome reconstitution ability with DNAs. Nucleosome disassembly experiments for the Widom 601 sequence detected by Förster resonance energy transfer and fluorescence thermal shift assays demonstrated that nucleosome disassembly is the inverse process of assembly and can be described as three distinct stages: opening phase of the (H2A–H2B) dimer/(H3–H4)2 tetramer interface, release phase of the H2A–H2B dimers from (H3–H4)2 tetramer/DNA and removal phase of the (H3–H4)2 tetramer from DNA. Our kinetic model of nucleosome assembly and disassembly allows to confirm that nucleosome assembly and disassembly in vitro are governed by chemical kinetic principles.